Exploration of the Concept of Light Duality through Quantum Interference Simulation: A Virtual Laboratory-Based Approach - Permono Adi Putro; Suryana, Vidya Az-zahra; Sinta Nopianti (Universitas Mandiri, 2025)
The phenomenon of light duality is a fundamental concept in modern physics that states that light has a dual nature, namely as a wave and a particle. Understanding this concept often becomes a challenge in learning due to the limitations of laboratory facilities to directly observe interference and diffraction phenomena. This study aims to explore the concept of light duality through quantum interference simulations based on a virtual laboratory using PhET Interactive Simulations from the University of Colorado Boulder. The research was conducted in a descriptive-quantitative manner by varying three main parameters, namely the number of slits (1, 2, and 3), slit width (0.04–0.4 mm), and light wavelength (400–700 nm). Each configuration was systematically simulated to observe the resulting diffraction and interference patterns. Data analysis was carried out using descriptive and inferential statistics, including Shapiro-Wilk, Levene, Kruskal-Wallis tests, as well as one-way ANOVA to identify the relationship between optical variables and the characteristics of interference patterns. The research results indicate that with variations in the number and width of slits, light tends to behave like particles with concentrated intensity, whereas with variations in wavelength, the widening light-dark pattern demonstrates wave properties. These findings reinforce the concept of light duality and confirm the effectiveness of virtual laboratories as a learning medium for visually and interactively understanding complex quantum phenomena.